Uptake and Intracellular Trafficking Studies of Multiple Dye-Doped Core-Shell Silica Nanoparticles in Lymphoid and Myeloid Cells - Sola F; Canonico B; Montanari M; Volpe A; Barattini C; Pellegrino C; Cesarini E; Guescini M; Battistelli M; Ortolani C; Ventola A; Papa S (Nanotechnology, Science and Applications, 2021)
Federica Sola,1,2 Barbara Canonico,1 Mariele Montanari,1 Angela Volpe,2 Chiara Barattini,1,2 Chiara Pellegrino,2 Erica Cesarini,1 Michele Guescini,1 Michela Battistelli,1 Claudio Ortolani,1 Alfredo Ventola,2 Stefano Papa1 1Department of Biomolecular Sciences, University of Urbino Carlo Bo, Urbino, PU, 61029, Italy; 2AcZon Srl, Monte San Pietro, BO, 40050, ItalyCorrespondence: Barbara CanonicoDepartment of Biomolecular Sciences, University of Urbino Carlo Bo, Via Ca’ Le Suore 2-4, Urbino, PU, 61029, ItalyTel +39 0722 304280Email barbara.canonico@uniurb.itIntroduction: Since most biologically active macromolecules are natural nanostructures, operating in the same scale of biomolecules gives the great advantage to enhance the interaction with cellular components. Noteworthy efforts in nanotechnology, particularly in biomedical and pharmaceutical fields, have propelled a high number of studies on the biological effects of nanomaterials. Moreover, the determination of specific physicochemical properties of nanomaterials is crucial for the evaluation and design of novel safe and efficient therapeutics and diagnostic tools. In this in vitro study, we report a physicochemical characterisation of fluorescent silica nanoparticles (NPs), interacting with biological models (U937 and PBMC cells), describing the specific triggered biologic response.Methods: Flow Cytometric and Confocal analyses are the main method platforms. However TEM, NTA, DLS, and chemical procedures to synthesize NPs were employed.Results: NTB 700 NPs, employed in this study, are fluorescent core-shell silica nanoparticles, synthesized through a micelle-assisted method, where the fluorescence energy transfer process, known as FRET, occurs at a high efficiency rate. Using flow cytometry and confocal microscopy, we observed that NTB 700 NP uptake seemed to be a rapid, concentration-, energy- and cell type-dependent process, which did not induce significant cytotoxic effects. We did not observe a preferred route of internalization, although their size and the possible aggregated state could influence their extrusion. At this level of analysis, our investigation focuses on lysosome and mitochondria pathways, highlighting that both are involved in NP co-localization. Despite the main mitochondria localization, NPs did not induce a significant increase of intracellular ROS, known inductors of apoptosis, during the time course of analyses. Finally, both lymphoid and myeloid cells are able to release NPs, essential to their biosafety.Discussion: These data allow to consider NTB 700 NPs a promising platform for future development of a multifunctional system, by combining imaging and localized therapeutic applications in a unique tool.Keywords: nanoparticles, uptake, intracellular trafficking, exocytosis, multifunctional tool